Biogeochemical investigations of marine methane seeps, Hydrate Ridge, Oregon - Valentine, D. L.; Kastner, M.; Wardlaw, G. D.; Wang, X. C.; Purdy, A.; Bartlett, D. H. (Journal of Geophysical Research-Biogeosciences, 2005)
[1] A series of biogeochemical studies were conducted at the southern summit of Hydrate Ridge, offshore Oregon. Using the submersible DSV Alvin, sediment push cores were collected from two distinct seep environments characterized by the presence of clam fields (CF) or microbial mats (MM) at the sediment-water interface; samples were also collected from a nearby reference site characterized by a barren surface at the sediment-water interface. Sediment samples from each setting were analyzed for the depth distributions of total organic carbon (concentrations, delta C-13 and Delta C-14), total sedimentary nitrogen, and microbial abundance. Pore fluids were extracted and analyzed for sulfate, alkalinity, sulfide, organic carbon, and volatile organic acids. These depth distributions clearly indicate the presence of three distinctive biogeochemical settings in the surface sediments of Hydrate Ridge, and provide the basis for a comparative biogeochemical analysis. Both CF and MM sites display properties indicating enhanced microbial activity in the subsurface, compared with the reference site. MM sites display evidence of net biomass production in the subsurface; however, a loss of sediment nitrogen relative to the reference site indicates that mineralization is also enhanced. Calculations based on the removal of nitrogen indicate that greater than 30% of autochthonous organic material is lost to enhanced mineralization in the top 23 cm of one MM site. An isotope mass balance of sediment-bound organic carbon indicates a mixed source, including methane and allochthonous organic carbon dissolved in the seep fluids. The concentrations of organic carbon dissolved in seep fluids reach values of 22 mM and provide a first indication that advective transport of dissolved organic carbon from great depth may supply an important source of energy and carbon to "methane seep'' communities.
090wnTimes Cited:19 Cited References Count:72
Keywords: anaerobic oxidation; authigenic carbonates; cascadia convergent margin; community structure; dissolved organic-carbon; fluid-flow; ne pacific; odp site 892b; phylogenetic analysis; sulfate-reducing bacteria

A decrease in discharge-normalized DOC export by the Yukon River during summer through autumn - Striegl, R. G.; Aiken, G. R.; Dornblaser, M. M.; Raymond, P. A.; Wickland, K. P. (Geophysical Research Letters, 2005)
Climate warming is having a dramatic effect on the vegetation distribution and carbon cycling of terrestrial subarctic and arctic ecosystems. Here, we present hydrologic evidence that warming is also affecting the export of dissolved organic carbon and bicarbonate (DOC and HCO3-) at the large basin scale. In the 831,400 km(2) Yukon River basin, water discharge (Q) corrected DOC export significantly decreased during the growing season from 1978 - 80 to 2001 - 03, indicating a major shift in terrestrial to aquatic C transfer. We conclude that decreased DOC export, relative to total summer through autumn Q, results from increased flow path, residence time, and microbial mineralization of DOC in the soil active layer and groundwater. Counter to current predictions, we argue that continued warming could result in decreased DOC export to the Bering Sea and Arctic Ocean by major subarctic and arctic rivers, due to increased respiration of organic C on land.
985cuTimes Cited:163 Cited References Count:28
Keywords: alaska; arctic-ocean; climate-change; CO2; discontinuous permafrost; dissolved organic-carbon; flux; MATTER; tundra

The Ocean Margins Program: an interdisciplinary study of carbon sources, transformations, and sinks in a temperate continental margin system - Verity, P. G.; Bauer, J. E.; Flagg, C. N.; DeMaster, D. J.; Repeta, D. J. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
The cycling of carbon on the US east coast shelf and upper slope has been studied for 20 years in a variety of interdisciplinary programs focused on the, Mid and South Atlantic Bights. The culmination of this research was a comprehensive field study conducted in 1996 to ascertain whether the Cape Hatteras shelf was a net source or sink for atmospheric CO(2), and the associated transformations and pathways of inorganic and organic carbon. The rationale, objectives, design, and overview of the Ocean Margins Program are given here as a framework to interpret the results of the papers presented in this special issue. (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:26 Cited References Count:96
Keywords: cape-hatteras; chesapeake bay; co2 fluxes; coastal zone; dissolved organic-carbon; gulf-stream; middle atlantic bight; north-carolina; slope sediments; united-states